RETRACTED: How Does Energy Efficiency Mitigate Carbon Emissions Without Reducing Economic Growth in Post COVID-19 Era - Li, Min; Yao-Ping Peng, Michael; Nazar, Raima; Ngozi Adeleye, Bosede; Shang, Meng; Waqas, Muhammad (Frontiers in Energy Research, 2022)
A comprehensive analytical study to assess the performance level of industrial function in the environment has been becoming necessarily valuable and the need of the present time. According to existing research, the COVID-19 pandemic resulted in a significant reduction in carbon emissions in 2020. The policymakers are focusing on the discrepancies and negative externalities of the environment caused by industries during their routine operations. This study aims to estimate the performance level of energy in the context of the environment of the countries which are members of the European Union (EU). This assessment is made through the Data Envelopment Analysis (DEA) model through which we can apply non-proportional adjustments taking into account the inputs of energy and its undesirable out puts. DEA model allows dynamic assessment of sources in the field of measuring energy efficiency and its environmental effects. The score of measurement of efficiency lies between zero to one which describes that China and Russia are bearing this score as one (1) which shows the highest level of efficiency in clean energy. The emission level of reduction of Green House Gases GHG in the first world countries is found better in the context of improvement of performance enhancement in the sector of the energy mix. The score of evasion is measured as 365 kt of CO2. This score for NO2 is 280kt and for SO2 is 82kt whereas it is 23 kt (0.24 kg/cap) of particulate hazards matter. The higher performance level of energy yields a negative relationship with emissions of gases with a significant number of 12% for NO2 in 2000 as compared to 13% of SO2 and 14% of PM2.5. Whereas the highest number of 18% is found for PM10. The regional public policymakers may enhance the facilitation system for better free trade and a result-oriented corporation environment to enhance the performance level of energy in the electric sector.